Research advances in treatment of neurological and psychological diseases by acupuncture at the Acupuncture Meridian Science Research Center - Lee, Bombi; Kim, Seung-Nam; Park, Hi-Joon; Lee, Hyejung (Integrative medicine research, 2014)
Acupuncture is an ancient therapeutic intervention that can be traced back at least 2100 years and is emerging worldwide as one of the most widely used therapies in the field of complementary and alternative medicine. Due to limitations associated with Western medicine's focus on the treatment of diseases rather than on their causes, interests are shifting to complementary and alternative medicines. The Acupuncture and Meridian Science Research Center (AMSRC) was established in 2005 to elucidate the neurophysiological mechanisms of acupuncture for neurological diseases based on multidisciplinary research supported by the Korean Ministry of Science and Technology. In the AMSRC, resultant research articles have shown that acupuncture can improve neurological and psychological problems, including Parkinson's disease, pain, and depression, in animal models. Basic research studies suggest its effectiveness in treating various problems such as depression, drug addiction, epilepsy, ischemia, dementia, Parkinson's disease, and pain. We strongly believe that these effects, evident from the AMSRC research results, can play leading roles in the use of acupuncture for treating neurological diseases, based on collaboration among various academic fields such as neurophysiology, molecular genetics, and traditional Korean medicine.